Evidence and modeling of 3D divertor footprint induced by lower hybrid waves on EAST with tungsten divertor operations. (26th October 2017) - Feng, W.; Wang, L.; Rack, M.; Liang, Y.; Guo, H.Y.; Xu, G.S.; Xu, J.C.; Liu, J.B.; Sun, Y.W.; Jia, M.N.; Yang, Q.Q.; Zhang, B.; et al.
Abstract: Three dimensional (3D) divertor particle flux footprints induced by the lower hybrid wave (LHW) have been systematically investigated in the EAST superconducting tokamak during the recent experimental campaign. We find that the striated particle flux (SPF) peaks away from the strike point (SP) closely fit the pitch of the edge magnetic field line for different safety factors q 95, as predicted by a field line tracing code taking into account the helical current filaments (HCFs) in the scrape-off-layer (SOL). As LHW power increases, it requires the fuelling to be increased e.g. by super molecular beam injection (SMBI), to maintain a similar plasma density, which may be attributed to the pump-out effect due to LHW, and may thus be beneficial for EAST steady state operations. The 3D SPF structure is observed with a LHW power threshold ( P LHW 0.9 MW). The ratio of the particle fluxes between SPF and outer strike point (OSP), i.e. Γ i o n, S P F / Γ i o n, O S P, increases with the LHW power. Upon transition to divertor detachment, the particle flux at the main OSP decreases, as expected, however, the particle flux at SPF continues increasing, in contrast to the RMP-induced striations that vanish with increasing divertor density. In addition, we also find that the in–out asymmetry of the 3D particle flux footprint pattern exhibits a clear dependence on the toroidal field direction (B × ∇ B ↓ and B × ∇ B ↑). Experiments using neon impurity seeding show a promising capability in 3D particle and heat flux control on EAST. LHW-induced particle and heat flux striations are also present in the H-mode plasmas, reducing the peak heat flux and erosion at the main strike point, thus facilitating long-pulse operation with a new steady-state H-mode over 60 s being recently achieved in EAST.